Mesenchymal Behavior of the Endothelium Promoted by SMAD6 Downregulation Is Associated With Brain Arteriovenous Malformation Microhemorrhage. Issue 7 (July 2020) - Fu, Weilun; Huo, Ran; Yan, Zihan; Xu, Hongyuan; Li, Hao; Jiao, Yuming; Wang, Linjian; Weng, Jiancong; Wang, Jie; Wang, Shuo; Cao, Yong; Zhao, Jizong
Abstract : Background and Purpose: In unruptured brain arteriovenous malformations (bAVMs), microhemorrhage portends a higher risk of future rupture and may represent a transitional state along the continuum of destabilization. Exploration of the molecular and cellular mechanisms of microhemorrhage will provide a possible target for medical treatment to prevent bAVM bleeding. Methods: We performed RNA sequencing analysis on 34 unruptured bAVM surgical samples. Functional pathway analysis was performed to identify potential signals associated with the microhemorrhagic phenotype. Candidate gene was then investigated in bAVM specimens by immunohistochemical staining. Several functional assays were used to investigate the effects of candidate genes on the phenotypic properties of cultured human umbilical vein endothelial cells. Then, Masson trichrome staining and immunofluorescence staining were used to evaluate the phenotypic and molecular changes in bAVM tissue. Results: Via RNA sequencing, we identified differential gene expression between 18 microhemorrhagic bAVMs and 16 nonmicrohemorrhagic bAVMs. TGFβ (transforming growth factor-beta)/BMP (bone morphogenetic protein) signaling was associated with the bAVM microhemorrhage group when SMAD6 (SMAD family member 6) was downregulated. Immunohistochemical staining showed that the vascular endothelium of microhemorrhagic bAVMs exhibited decreased SMAD6 expression. Functional assays revealed that SMAD6 downregulation promoted the formation of endothelial cell tubes with deficient cell-cell junctions and facilitated the acquisition of mesenchymal behavior by endothelial cells. Masson trichrome and immunofluorescence staining demonstrated that mesenchymal phenotype of endothelial cells is promoted in microhemorrhagic bAVMs. Conclusions: TGFβ/BMP signaling mediated by SMAD6 in vascular endothelial cells is associated with microhemorrhagic bAVMs, and mesenchymal behavior of endothelial cells induced by SMAD6 downregulation is related with bAVM microhemorrhage. Abstract : Supplemental Digital Content is available in the text.